2013
DOI: 10.3945/ajcn.112.054478
|View full text |Cite
|
Sign up to set email alerts
|

Zinc supplementation reduces morbidity and mortality in very-low-birth-weight preterm neonates: a hospital-based randomized, placebo-controlled trial in an industrialized country

Abstract: Background: Zinc plays a pivotal role in the pathogenesis of many diseases and in body growth. Preterm neonates have high zinc requirements. Objective: The objective of the study was to investigate the efficacy of zinc supplementation in reducing morbidity and mortality in preterm neonates and to promote growth. Design: This was a prospective, double-blind, randomized controlled study of very-low-birth-weight preterm neonates randomly allocated on the seventh day of life to receive (zinc group) or not receive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(85 citation statements)
references
References 47 publications
1
84
0
Order By: Relevance
“…Recent studies showed influence of dietary micronutrient intake on the occurrence of infections. Most of these studies have been done in developing countries [19] in specific patient groups [20], or do not present data about infections [21]. It is difficult to extrapolate these study results to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed influence of dietary micronutrient intake on the occurrence of infections. Most of these studies have been done in developing countries [19] in specific patient groups [20], or do not present data about infections [21]. It is difficult to extrapolate these study results to other populations.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that oral supplementation reduced the incidence of necrotizing enterocolitis and overall morbidity and mortality in this population (Terrin et al, 2013). Zinc-fortified formula improved delayed-type hypersensitivity, skin test reactivity, lymphoproliferative response, and increased salivary IgA (Shah and Sachdev, 2006;Schlesinger et al, 1992).…”
Section: Malnutrition Nutrient Deficiency and Infectionmentioning
confidence: 98%
“…Attempts to enhance gastrointestinal development and protect against infection and necrotizing enterocolitis have included use of prebiotics and probiotics, which bolster development of the microbiota. A recent study showed that although enteral supplementation with a prebiotic mixture of neutral and Protein calorie malnutrition, dietary deficiency (Moynahan, 1974;Stevens and Lubitz, 1998), high phytate (Moynahan, 1974;Stevens and Lubitz, 1998), transport deficiency (Moynahan, 1974;Stevens and Lubitz, 1998) Supplementation in infection (Stafford et al, 2013) Prenatal maternal supplement (Shah and Sachdev, 2006;Wieringa et al, 2010) Maternal supplementation (Terrin et al, 2013) Infant supplementation (Osendarp et al, 2007;Osendarp et al, 2006) Thymic atrophy, lymphopenia altered T-cell subsets, (Youn et al, 2008;Smith et al, 2008) Humans (Chen, 2012) HIV-1 infection (Shah and Sachdev, 2006;Wieringa et al, 2010;Smith et al, 2008) ↑Microbial diversity, composition, & colonization (Kasaikina et al, 2011) Required for glutathione peroxidase activity ↓NF-κB activity, enhanced virulence of coxsackie B virus Deficiency in HIV-1 linked to progression, antiretroviral therapy increased levels acidic oligosaccharides did increase early postnatal intestinal colonization with a trend toward increased bifidobacteria, extensive use of broad-spectrum antibiotics counteracted the growth of all intestinal microbiota and delayed normal microbiota development (Westerbeek et al, 2013).…”
Section: Influence Of Nutrients In Priming and Development Of The Gasmentioning
confidence: 99%
“…Thus, premature neonates have relatively high dietary zinc requirements. Recently, it has been demonstrated that dose of zinc higher than those recommended (Table 3) may reduce incidences of NEC, but not of infectious diseases in preterm neonates (Terrin et al 2013). Other studies evaluating the role of zinc in preventing infections in the first months of life are summarized in Table 3.…”
Section: Zinc Supplementationmentioning
confidence: 99%
“…Zinc is a structural component of hormones, nucleotides, and proteins (Terrin et al 2013); it is required for the production of a wide variety of enzymes involved in essential metabolic patterns (i.e., protein synthesis, nucleic acid metabolism, immune functions, and organogenesis). Zinc is considered key for optimal functioning of both innate and acquired immunity.…”
Section: Zincmentioning
confidence: 99%